Re-evaluating the Hierarchy of Evidence: What is the Gold Standard? - Tang, Brandon; Wan, Stephanie J. (The Meducator, 2014)
On October 16, 1846, William Morton took part in an operation to remove a tumour from a patient’s neck. However, this surgery was unlike any other that had been completed before. 1 Morton’s stage was the local surgical amphitheater in the Massachusetts General Hospital, and his main prop was the ether, a novel substance that promised to alleviate pain in an unprecedented manner. Within the amphitheater, scientists, dentists, and doctors eagerly awaited the awakening of Morton’s patient after the surgery. To everyone’s delight, after awakening, the patient announced that he did not feel any pain during the operation. Barely a month later, this local stage turned global when Henry Jacob Bigelow published this case study in the Boston Medical & Surgical Journal. 2,3 To this date, the birth of anesthesia is considered a landmark medical discovery.